THE INFLUENCE OF DECENTRALIZED FINANCE (DEFI) ON GLOBAL FINANCIAL STABILITY: AN EMERGING CHALLENGE - Loso Judijanto; I Ketut Kusuma Wijaya; Krisdiana Krisdiana; Imam Jayanto; Samuel PD Anantadjaya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Decentralized Finance (DeFi) has emerged as a transformative force in the financial sector, offering peer-to-peer financial services without traditional intermediaries such as banks. By utilizing blockchain technology and smart contracts, DeFi enables greater accessibility, transparency, and efficiency in financial transactions. However, the rapid expansion of DeFi poses significant challenges to global financial stability. This literature review explores the impact of DeFi on systemic risks, regulatory frameworks, and the traditional banking sector. While DeFi offers opportunities for financial inclusion and innovation, it also introduces new risks related to cybersecurity, liquidity, and market volatility. The absence of standardized regulations across jurisdictions exacerbates these risks, creating vulnerabilities in the global financial system. Furthermore, the interconnection between DeFi markets and traditional financial institutions increases the potential for spillover effects during periods of financial stress. This paper highlights the need for a balanced regulatory approach that fosters innovation while safeguarding financial stability. As DeFi continues to evolve, understanding its influence on global financial stability becomes increasingly important for policymakers, regulators, and financial institutions.